Improvisation of agri-horticultural interventions based on matrix ranking - Agrawal, R.K.; ., Satyapriya; Singh, J.B.; Singh, Ramesh; Kumar, Sunil; Sharma, P.; Shukla, Deepty; Kumari, Shyama (Indian Journal of Agroforestry, 2020)
A Participatory Rural Appraisal (PRA) study under NICRA project was conducted for assessing the relative importance of different arable and horticulture crops and livestock, problem identification and prioritization of interventions for augmenting the agri/ horticultural production to ensure the secured livelihood of farmers of Kadesara Kalan village situated in Lalitpur District of Uttar Pradesh. On the basis of matrix ranking, wheat and groundnut were ranked as the most preferred crops due to higher yield, more income during rabi and kharif seasons, respectively. In farmer’s view, the income followed by market price, irrigation requirement and suitability to soil remained the important criteria for choosing a crop. Among the matrix ranking of vegetables/spices, ginger proved most preferred crop of this group, because of more income, high value and market availability followed by tomato, turmeric, brinjal, chilies and potato. Fruit trees like aonla, guava, zizyphus, mango, papaya, citrus, wood apple, mulberry and jack fruit are grown in the village in sporadic pockets, but citrus and papaya were the dominant fruits followed by anoia, guava, ber etc. based on the parameters like easy availability of market, domestic consumption, market price, suitability to kitchen garden etc.